Lycophytes and Ferns of Nedumangad to Kulashekaram, Southern Western Ghats of India - Alex Christon, R.; Johnson, M. (Indian Forester, 2021)
The present investigation was undertaken to enumerate the lycophytes and ferns of Nedumangad to Kulashekaram. Nedumangad to Netta (8°36′19″ N to 8°26′51″ N latitude and 77°0′4″ E to 77°13′24″ E longitude) and Netta to Kulasekharam (8°26′51″ N to 8°22′5″ latitude and 77°13′24″ E to 77°17′55″ E longitude) lies in the Southern Western Ghats at an altitude of Nedumangad to Netta is 55-193 m and 46-130 m for Netta to Kulasekharam. From Nedumangad to Kulashekaram, 2 lycophytes and 29 ferns belong to 19 genera and 12 families are recorded. Among the 12 observed families, Pteridaceae and Thelypteridaceae are dominant with twelve and eight species respectively. Among the 31 observed species, 28 species are terrestrial ferns, one epiphytic ferns (Aglaomorpha quercifolia (L.) Hovenkamp & S. Linds.,) and one aquatic ferns (Marsilea minuta L.) and one climber (Lygodium flexosum (L.) Sw).